Դեռահասների միջանձնային փոխհարաբերություններում դրսևորվող սոցիալական ընկալման յուրահատկությունները - Աննա Գևորգյան (ՀՀ ԳԱԱ հրատ.)
In the present article on attempt has been made to reveal the interpersonal relations of the teenagers with grown-ups and the peers. Reforming the same socializing role these two types of interrelations may oppose to each other with their character and norms and have their influence on the teenagers’ social perception, which is described in the article in details. The results of our experiments have also been included in the article.
Keywords: Philosophy; Psychology; Religion; Psychology